Long-term Clinical Outcome After Descemet Membrane Endothelial Keratoplasty - Schlögl, Andreas; Tourtas, Theofilos; Kruse, Friedrich; Weller, Julia M. (American Journal of Ophthalmology, 2016)
To evaluate the long-term clinical outcome up to 5 years after Descemet membrane endothelial keratoplasty (DMEK).Retrospective, consecutive case series.In this single-center study, 310 consecutive DMEK operations for endothelial decompensation were reviewed; 97 eyes of 84 patients met the inclusion criterion of a minimum 3-year follow-up. Retrospective evaluation of clinical examinations occurred at 1 and 3 months and annually up to 5 years after DMEK at the Department of Ophthalmology, Friedrich-Alexander-University Erlangen-Nürnberg, Erlangen (FAU), Germany. Main outcome measures were corrected distance visual acuity (CDVA), endothelial cell density (ECD), central corneal thickness (CCT), and graft survival (Kaplan-Meier analysis).Mean follow-up was 53 ± 13 months. CDVA improved from 0.62 ± 0.42 logMAR before DMEK to 0.13 ± 0.12 logMAR (P < .001); 57% of eyes without ocular comorbidities reached >=20/25 at 5 years after DMEK. ECD was stable after the initial postsurgical decrease (42% at 1 month, 44% at 5 years), from 2602 ± 243 cells/mm(2) before DMEK to 1460 ± 179 cells/mm(2) at 5 years. CCT decreased from 644 ± 67 ?m before DMEK to 557 ± 49 ?m at 5 years, with a minimum (530 ± 54 ?m) at 3 months. Cumulative probability of 5-year graft survival was 95%.The long-term sustainability of DMEK was confirmed. DMEK not only provides fast visual rehabilitation but maintains its clinical outcome within a follow-up of 5 years. Visual acuity and endothelial cell loss remain stable between 3 months and 5 years after DMEK.
EVALuna2:21324